Revolutionising finance for agricultural value chains - Rutten, Lamon; Addom, Benjamin K. (Technical Centre for Agricultural and Rural Cooperation, 2014)
Lamon Rutten and Benjamin Addom discuss the far-reaching changes that are needed to revolutionise finance for agri-value chains